2017
DOI: 10.32831/jik.v6i1.155
|View full text |Cite
|
Sign up to set email alerts
|

Kemampuan Ibu Melakukan Stimulasi Untuk Perkembangan Bayi Usia 3-6 Bulan Di Wilayah Kerja Puskesmas Puhjarak

Abstract: Stimulation is one of the factors that affect a child’s development. The age of 3-6 months is included in the first 1000 days of life which is a critical period in which the child's brain begins to develop. Mothers can stimulate children according to their developmental stages. During infancy, a close relationship exists between the mother and child, so the influence of mother in educating the childis very big. The purpose of this study is to find out the correlation between the mothers ability to stimulate 3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
4
Order By: Relevance
“…(Zhong, He, Gao, Wang, & Luo, 2020) Ibu yang memiliki pengetahuan dan kemampuan melakukan stimulasi berpengaruh pada perkembangan bayi umur 3-6 bulan. (Destiana, Yani, & Yanuarini, 2017) Orangtua yang memiliki pengetahuan, cenderung lebih terlibat dalam aktivitas dengan anak dan akan menyediakan bahan permainan dengan jumlah yang lebih banyak dan bervariasi sehingga akan dapat meningkatkan perkembangan anak. (Zhong et al, 2020) Anakanak yang berasal dari keluarga dengan tingkat ekonomi kurang dapat mengalami kesulitan untuk mencapai potensi tertinggi mereka jika orangtua tidak memperoleh intervensi untuk melakukan stimulasi.…”
Section: Pembahasanunclassified
“…(Zhong, He, Gao, Wang, & Luo, 2020) Ibu yang memiliki pengetahuan dan kemampuan melakukan stimulasi berpengaruh pada perkembangan bayi umur 3-6 bulan. (Destiana, Yani, & Yanuarini, 2017) Orangtua yang memiliki pengetahuan, cenderung lebih terlibat dalam aktivitas dengan anak dan akan menyediakan bahan permainan dengan jumlah yang lebih banyak dan bervariasi sehingga akan dapat meningkatkan perkembangan anak. (Zhong et al, 2020) Anakanak yang berasal dari keluarga dengan tingkat ekonomi kurang dapat mengalami kesulitan untuk mencapai potensi tertinggi mereka jika orangtua tidak memperoleh intervensi untuk melakukan stimulasi.…”
Section: Pembahasanunclassified
“…Ibu sangat berperan dalam stimulasi dan deteksi dini penyimpangan perkembangan. Gangguan pertumbuhan dan perkembangan yang ditemukan lebih awal akan mendapatkan intervensi sangat berharga untuk mencegah kecacatan permanen (Destiana, Yani & Triatmi, 2017). Orang tua…”
Section: Hasil Dan Pembahasanunclassified
“…Based on Destian's 2017 research, which examined the mother's ability to stimulate the development of babies aged 3-6 months, it showed that early detection is important in finding growth and development disorders in children. Growth and development disorders that are found early will receive very valuable interventions to prevent permanent disability (Destiana, Yani, & Triatmi, 2017).…”
Section: Introductionmentioning
confidence: 99%